Association between Dietary Habits and Parental Health with Obesity among Children with Precocious Puberty - Yong Hee Hong; Yeon Ju Woo; Jong Hyun Lee; Young-Lim Shin; Hee-Sook Lim (MDPI AG, 2020)
Precocious puberty, resulting in various physical, mental, and social changes, may have negative consequences for children and their families. In this study, we investigated whether there were differences between parental obesity, children's and parent's awareness of body shape, and dietary habits according to obesity levels in children with precocious puberty. A total of 193 children (93.3% girls) diagnosed with precocious puberty were classified into three groups according to their obesity levels. Negative body shape awareness and dissatisfaction were significantly higher in the obese group than in the normal-weight group, and parents were more likely to perceive their children as fat than the children themselves. In addition, the obesity rate of parents in the obese group was higher, and the body mass indexes of children and parents were significantly correlated. The nutrition quotients (NQs) were revealed to be significantly lower in the obese group with significantly lower scores. The significant factors related to obesity were the awareness of a fatty body image and dissatisfaction, obesity of the parents, and the NQ. The results show that obese children with precocious puberty were more vulnerable to negative lifestyle, family environment, and self-esteem effects than their normal-weight peers. Therefore, various interventions, such as environmental management, psychological support, and nutrition education, are needed that focus on the obesity and health conditions of children with precocious puberty.